Selective oxidation conversion of methanol/dimethyl ether. Issue 30 (18th March 2022) - Gao, Xiujuan; Zhang, Junfeng; Song, Faen; Zhang, Qingde; Han, Yizhuo; Tan, Yisheng
Abstract : Synthesizing high value-added oxygenated chemicals through the oxidation process is a new and important research direction for high-quality conversion of methanol/DME. Abstract : As important platform compounds, methanol and dimethyl ether (DME) are vital bridges between the coal chemical, petrochemical and fine chemical industries. At present, the synthesis of methanol/DME has been industrialized, and the production capacity is much larger than the market demand. Therefore, the conversion of methanol/DME into more valuable chemicals is an important and significant topic. The synthesis of high value-added oxygenated chemicals and diesel oil additives from methanol/DME by an oxidation method has attracted substantial attention due to it being green and environmentally friendly and having good atom economy. In this feature article, we have summarized the recent advances in the synthesis of formaldehyde, methyl formate, dimethoxymethane, and polyoxymethylene dimethyl ethers, from the selective oxidation of methanol/DME, and further discussed the adsorption and activation of reactant molecules, selective cleavage of C–O, C–H or O–H bonds in methanol/DME molecules and the C–O chain growth in the target products. In the end, major challenges and future prospects are proposed from the viewpoint of catalyst design and application. It is expected that this feature article will provide theoretical guidance for the activation and cleavage of C–O, C–H, or O–H bonds in other small molecules of alcohol/ether as well as low-carbon alkanes, so as to synthesize high value-added chemicals.